Idiom translation strategies in Netflix subtitle of Habibie and Ainun : A comparative study with DeepSeek-V3.2 - Khairun Najmi; Mohamad Zaka Al Farisi; Rinaldi Supriadi (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2026)
This research aims to analyze idiom translation strategies in the Netflix subtitles of the film Habibie and Ainun and to compare them with the machine translation generated by DeepSeek-V3.2 based on Baker’s (1992) classification. Idioms expressions are one of the most problematic areas in audiovisual translation due to their literalness and cultural embodiment. Descriptive qualitative is used as the research methods in this research with 22 Indonesian idioms classified according to Fernando (1996) to which a comparative analysis was made investigate the use and diffusion of translation strategies, namely idioms of similar meaning and form, idioms of similar meaning but different form, paraphrase, and omission. The results suggest that the paraphrase strategy is also the dominant one across both human and machine translations, reflecting a stronger emphasis on achieving meaning understanding rather than idiomatic form. The strategies of idioms of similar meaning and form and idioms of similar meaning but different form in the TL are tendencies rather than strict rules, and they vary from case to case depending on the existence of idiomatic equivalents in Arabic, while omission is not identified this indicates that the source idiom are preserved for coherence. The results also show that human translators consider the narrative setting and emotional meaning, while machine translation focuses mainly on semantic equivalence. This study offers to Indonesian–Arabic translation studies and demonstrates the effectiveness of AI-based translation systems in controlling contextual and culture-specific idioms.